2006
DOI: 10.1086/507523
|View full text |Cite
|
Sign up to set email alerts
|

Deep Imaging Surveys of Star-forming Clouds. IV. The Meek and the Mighty: Outflows from Young Stars in Chamaeleon I

Abstract: We present a survey of shocks and outflows in the Chamaeleon I star-forming complex using H , [S ii], and SDSS i 0 images obtained from the ground, an i 0 image obtained with the Hubble Space Telescope, and 4.5 m images obtained with the Infrared Array Camera (IRAC) on the Spitzer Space Telescope. We find new Herbig-Haro ( HH ) objects and extensions to the previously cataloged shocks that trace parts of at least 20 distinct outflows from young stars. Some HH objects mark the presence of giant outflows, the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…A search in the literature reveals no detections of an outflow associated with Glass Ib. The nearest Herbig-Haro outflow, HH 935, has a separation of 92 north of the Glass I system, but it is moving southward (Bally et al 2006). The 2008 Spitzer IRS spectrum did not show H 2 emission at 12.28 and 17.03 μm, which we would have expected if the fine-structure emission was in an outflow.…”
Section: Outflowmentioning
confidence: 70%
“…A search in the literature reveals no detections of an outflow associated with Glass Ib. The nearest Herbig-Haro outflow, HH 935, has a separation of 92 north of the Glass I system, but it is moving southward (Bally et al 2006). The 2008 Spitzer IRS spectrum did not show H 2 emission at 12.28 and 17.03 μm, which we would have expected if the fine-structure emission was in an outflow.…”
Section: Outflowmentioning
confidence: 70%
“…Bally et al (2006) suggested that ESO-Hα569 as the possible source for the Herbig Haro object 919. HH 919 is an arcminute-long filament with a PA of ∼60°-75°and is located  22 (0.05 pc) southwest of ESO-Hα569.…”
Section: Hst Jet Outflow Imagesmentioning
confidence: 99%
“…A YSO, Cha-MMS2, is located very close to Cha1-C7 and drives a bipolar outflow (see, e.g., Bally et al 2006;Reipurth et al 1996;Mattila et al 1989). We examined the possibility that the second, higher velocity component that we see in our spectra coincides with the redshifted outflow component.…”
Section: Multiple Velocity Componentsmentioning
confidence: 99%